Impact of educational intervention regarding anaemia and its preventive measures among adolescent girls of Government Arts College of Vadodara, Gujarat, India - Bhalsod, Ashish Shamjibhai; Dave, Nisarg N.; Thakor, Nilesh (International Journal of Advances in Medicine, 2019)
Background: The nutritional and the health needs of the adolescents more because of the growth spurt and the increase in physical activity. So, they are at high risk for anaemia and malnutrition. Objective was to assess knowledge of adolescent girls regarding anaemia and its preventive measures before and after educational interventional training. Methods: The present study was an interventional study undertaken in purposively selected Government Arts college of Vadodara city during June to September 2019. Total 100 adolescent girls between the age group of 17-19 were included after written informed consent. Baseline knowledge of adolescent girls regarding anaemia and its preventive measures was assessed by pre-designed, pre-tested and semi structured questionnaire. Single educational interventional training for 45 minutes was given to selected adolescent girls. Post-intervention knowledge of students for the same was assessed after training. Thus, collected data was analyzed using SPSS 17 (Trial Version). Results: Baseline knowledge of the adolescent girls regarding causes, signs and symptoms of anemia and dietary sources of iron was 23%, 40% and 25% respectively which was significantly increased to 66%, 72% and 55% respectively after the intervention. Baseline knowledge of the adolescent girls regarding factors which inhibit and increase iron absorption was 4% and 30% respectively which was significantly increased to 41% and 79 % respectively after the intervention. Baseline knowledge of the adolescent girls regarding treatment of anaemia was 21% which was significantly increased to 64 % after the intervention. Conclusions: Single educational session significantly improve the knowledge of adolescent girls regarding anaemia and its preventive measures.